Indonesian Historiography in Search of Identity - Kuntowijoyo Kuntowijoyo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2000)
With regard to the relation between the discipline and the society, being historians in Indonesia has been a kind of adventure. How is it possible? History proves to be a risky business. To be responsive to popular demand is doing good to their own society, but neglecting their own field of study. To be independent is also a wrong position, for it means doing bad to their own society and living in ivory tower. This paper is then firstly an attempt to reconcile the dilemma. Secondly, it is an attempt to solve the problem of how a historian can serve the time, without being a